A CONCEPTUAL STUDY ON ARBUDA (CANCER) AND ITS MANAGEMENT: A REVIEW - Rathiya, Kavita (International Journal of Ayurveda and Pharma Research, 2018)
Lifestyle disorders are one of the biggest problems for our society now days. Such types of diseases are mainly due to unhealthy diet, bad food habits, lack of physical activity etc. Cancer is one of the most dreaded diseases of the 20th century and spreading further with continuance and its incidence is increased in 21st century. It has become the most dangerous and popular lifestyle disease in the world. In Ayurveda, lifestyle diseases are diseases caused by Viruddha “Ahara” and “Vihara” (food and regimen).The science of Ayurveda is supposed to add a step on to the curative aspects of cancers that have resemblance with clinical entities of Arbuda and Granthi mentioned in Sushrutha Samhita. According to Ayurveda, most diseases connected with the psychophysiologic and pathologic changes in the body are caused by imbalance in three different Dosha (i.e, Vata, Pitta, and Kapha). Cancers (Arbuda) of the prostate, breast, lung, and colon, are most common in the Western world and are least common in the Eastern world. The therapeutic approach involves Prakritisthpani chikitsa (health maintenance), Rasayana Chikitsa (restoration to normal), Naishthiki Chikitsa (spiritual approach), and Roganashani Chikitsa. The article is written with an intention to raise awareness and encourage implementation of Ayurvedic therapies for combating cancer and suggesting an integrated approach in tumor management and treatment medications.